(untitled) (Research, Society and Development, 2021)
Motivated by the industrialization technological developments through the accidents at work worrying statistics, NR-12 was created to deal with Safety at Work in Machinery and Equipment. Based on this standard and with a health and safety engineer professional support, it is possible to analyze and make the necessary adjustments to the machinery. In the study it is possible to see the risks present and the safety at work importance on the ball mill, once a very common machine in the mining industry. The ball mill operation involves the forklift for loading, raw material that make up the material to be refined, and also work at height. In order to carry out maintenance on this machine, it is necessary for machinery maintenance employees to have training in NR-33 standard which addresses Work in Confined Space. Working with this equipment involves exposure to physical risks (such as noise and vibration) chemical risks, mechanical risks and ergonomic risks (considering that it is tiring work and requires intense effort from the worker). This article presents a proposal to adapt the work environment and equipment according to the NR-12 standard in order to eliminate or minimize the risks to which workers are exposed.